Design and Evaluation of ADDIE-Based Animated Video Instructional Materials for Enhancing Learning Outcomes in Primary Civic Education - Tuti Wahyuningsih; Muh. Fahrurrozi; Badarudin Badarudin; Syarifah Aulia (Sumber Belajar Sejahtera, 2026)
Materials to enhance learning outcomes in primary civic education. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted with second-grade students at SDN 01 Terara, involving a small group (n=6) and a large group (n=20). Data were collected through expert validation, questionnaires, and pretest–posttest assessments. The validation results showed that the instructional materials achieved an average score of 71%, categorized as valid. The practicality test indicated positive responses from teachers (70%) and students (70.1%), categorized as highly practical. The effectiveness analysis using the N-gain score revealed a moderate improvement in the small group (0.48) and a high improvement in the large group (0.58). These findings indicate that the developed animated video-based instructional materials are valid, practical, and effective in improving students’ learning outcomes. This study contributes to the field of educational technology by integrating multimedia learning with a systematic instructional design framework and providing empirical evidence of its effectiveness in primary civic education.